Influence of active recovery on professional rugby union player`s ability to harness postactivation potentiation - West, D.; Cunningham, D.; Bevan, H.; Crewther, B.; Cook, C.; Kilduff, L. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: After postactivation potentiation (PAP) has been induced, current research recommends that, on average, an 8 minute passive recovery period is applied before engaging in subsequent dynamic exercise. However, given the importance of maximizing time usage during the warm-up of elite athletes, it is likely that further exercise would be incorporated into this time frame. This study aimed to examine the effects of passive and active recovery on the ability to utilize PAP. Methods: In a randomised and counter balanced design, 36 professional rugby union players completed two experimental trials involving a baseline countermovement jump (CMJ), followed by a PAP stimulus (3 x 3 repetitions at 87% of 1-RM back squat) and CMJ retesting after 8 minutes of passive or active recovery. The active recovery involved subjects performing ballistic bench throws (1 x 3 repetitions at 30% 1-RM bench press) 4 minutes after the lower body PAP stimulus. Data presented as mean±SD. Results: Baseline peak power output (PPO) was not different between conditions (P=0.61). CMJ PPO increased from baseline under both conditions, however the delta (mean±SD; passive +161±127 vs. active +116±44 W; P=0.03) and % change (passive 3.3±2.8 vs. active 2.3±0.9 %; P=0.03) in PPO was greater after the passive recovery, when compared to the active recovery. Conclusion: In conclusion, the passive and active recovery periods both led to increases in lower-body PPO, nevertheless, the passive recovery elicited the greatest performance changes. However, the active recovery is a more practical option for athletes, as it maximizes time usage during warm-up.